A Model on Multiple Perspectives of Citizens’ Trust in using Social Media for E-Government Services - Khan, Sohrab; Zairah Ab. Rahim, Nor; Maarop, Nurazean (International Journal of Engineering and Technology, 2018)
The lack of trust has a critical role in discouraging citizens to use social media for e-government services. Therefore, developing trust is an essential need for making citizensâ€™ comfortable to participate in government social media services. Majority of previous studies on the relationship with trust between government and people have been conducted on e-government websites. Those studies are quite narrow in terms of their scope to address multiple aspects of citizens trust. On the contrary, the context of using social media for e-government services has not received much attention by previous researchers. This study proposes an integrated model of trust from multiple perspectives with an objective to identify those factors that can influence citizensâ€™ trust in context of using social media as a technology for e-government services. The constructs in the proposed model were integrated from the trust literature and Technology Acceptance Model (TAM). The findings reveal individual characteristics, government factors, risk factors and social media characteristics as multiple antecedents of citizenâ€™s trust to use social media for e-government services. A research instrument was developed and validated to examine the proposed model. A pilot study was conducted, and the instrument was refined based on its results. Â Â